Sickled Erythrocytes Reversal and Membrane Stabilizing Compounds in Telfairia occidentalis - Samuel Atabo; Ismaila Alhaji Umar; Dorcas Bolanle James; Aisha Indo Mamman (Scientifica)
Background and Purpose. Traditional management of sickle cell disease (SCD) is ubiquitous in Africa. In south-eastern Nigeria, Telfairia occidentalis (T. occidentalis) is strongly recommended for consumption by SCD patients, owing to its presumed therapeutic effect. This study investigates the antisickling and membrane regenerative potentials of T. occidentalis in sickled erythrocytes. Experimental Approach. Sickled erythrocytes obtained from SCD patients were treated with sodium metabisulphite (2%) to induce further sickling. Heat and hypotonic-induced lyses of red blood cells’ membranes were also carried out. The RBCs were treated with varying concentration (10.0, 1.0, and 0.1 mg mL−1 and 0.5, 1.0, 1.5, 2.0, and 2.5 mg mL−1, resp.) of T. occidentalis extracts as treatment regimen for in vitro antisickling and membrane stabilizing assays. Extract with peak activity was purified and reused in antisickling assay. Key Results. The antisickling activity of aqueous and methanolic extracts of leaves, seeds, and stem of Telfairia occidentalis at 10.0, 1.0, and 0.1 mg mL−1 revealed that the aqueous leaves extract (10 mg mL−1) exhibited the highest antisickling activity (64.03%) which was significantly (p<0.05) higher than that of the stem (47.30%) and seeds (37.50%). Partially purified fractions recorded improved antisickling effect (peak activity of 70%). Characterization (using GC-MS) of the most active fraction revealed some bioactive compounds. In the membrane stabilizing assay, methanolic and aqueous stem extracts of T. occidentalis showed the highest effect of 71.85% and 61.29%, respectively. Conclusions and Implications. The results provide scientific evidence for ethnopharmacological use of T. occidentalis in the management of SCD.